(untitled) (Scientific journal of the Fergana State University, 2023)
In the article, it is shown that soil is a complex object to evaluate its fruitfullness, as well as analyzed different methods in this sphere. It emphasises the integrity of the usage of models of soil on evaluating of its fertility, the soil has its characteristics and peculatities and its formation of fruitfulness are conditioned by definite conditions.